HPV6 e HPV11: vírus de baixo risco envolvidos na transformação maligna? - SILVA, Leandro Lima da (2023)
Introduction: Cancer is the disorderly growth of cells, which are directed to the surrounding tissues and organs. Among the factors that contribute to the increase of this pathology are the infectious agents that include viruses, bacteria and parasites, with the human papillomavirus (HPV) being strongly associated with cervical, anogenital and oropharyngeal cancers. HPVs are classified as high and low oncogenic risk. Among the high-risk HPVs, subtypes 16 and 18 are the most frequent in neoplasms associated with this virus and are the most aggressive. There are also low-oncogenic HPV subtypes, such as HPV 6, 11, which are mainly associated with benign lesions such as condyloma. Studies also suggest the involvement of low-risk HPVs in malignant non-cervical lesions. Methodology: The present study is a systematic review of the last 10 years to determine the prevalence of HPV6 and HPV11 infections in anogenital and head and neck cancers, evaluating their carcinogenic potential and comparing their viral genomes with the HPV16 genome to identify significant similarities and differences. The three standard databases in biomedicine: PubMed, Embase and Cochrane, accessed in March and April 2022, were used as the basis for carrying out the study. The keywords "cancer AND HPV6" or "cancer AND HPV11" were applied and 541 articles were retrieved from PubMed, 695 articles from Embase and 29 articles from Cochrane. Complete genomes of HPVs were retrieved from the RefSeq and GeneBank databases, both available at NCBI. Results: It was observed that low-risk HPV infections, associated with genital warts (condylomata) and low- grade dysplasias, are associated with a 1 to 3% risk of cancer progression if not resolved. It was also observed that monoinfections by HPV6 and HPV11 were mainly associated with cancers of the larynx and penis, with cancers of the uterine cervix, vagina, vulva, and head and neck (except pharynx) presenting the lowest frequencies of monoinfections by HPV6 and HPV11. The protein most similar in number of identical amino acids or similar chemical properties between HPV16 and HPV6 identified was E7, while the E5 protein had the least similarity. Similar results were obtained between HPV16 and HPV11. Conclusion: Head and neck studies mainly reported data from the larynx, which probably reflects the known role of HPV6 and HPV11 in respiratory papillomas in this anatomical area. The early E7 gene was more similar between high and low oncogenic risk HPVs. In addition, there were limitations such as the small number of cases in some studies added to the lack of data, resulting in the need to draw a cross-section from the moment of inoculation of the low-risk subtypes HPV 6 and 11 with their carcinogenic potential.